Mediasi Loyalitas pada Kompetensi dan Produktivitas Karyawan - Bonny Buntoro; Tjutju Yuniarsih; Eeng Ahman; Syamsul Hadi Senen (Universitas Winaya Mukti, 2022)
The level of success of the company can be measured through the work productivity of individuals who work in the company. To be able to predict the level of employee work productivity, employee competence has an important role in it. Employee loyalty has a role in mediating the effect of competence on the level of employee work productivity. PT A.W. Faber-Castell Indonesia faces the challenge of employee work productivity not achieving work targets. This study aims to examine the role of employee loyalty in mediating the effect of employee competence on work productivity at PT A.W. Faber-Castell Indonesia. The sample of this study is 250 employees from a population of 745 employees. The data collection technique was done by disproportionate stratified random sampling. Analysis technique using SEM PLS. The results of the analysis show that work loyalty is proven to mediate between employee competence and employee work productivity at PT A.W. Faber-Castell Indonesia. The results show that employee competence can have a significant and positive influence on employee work productivity, so in this case employee loyalty mediates the effect of employee competence on productivity. The implication of this research is that in an effort to increase employee productivity, PT A.W. Faber-Castell Indonesia can improve employee competence through training, which is accompanied by increased loyalty through involving employees in decision-making and establishing effective communication.